A clinical score for neuroendocrine tumor patients under consideration for Lu-177-DOTATATE therapy. Issue 3 (March 2021) - Das, Satya; Du, Liping; Schad, Aimee; Jain, Shikha; Jessop, Aaron; Shah, Chirayu; Eisner, David; Cardin, Dana; Ciombor, Kristen; Goff, Laura; Bradshaw, Marques; Delbeke, Dominique; et al.
Abstract : We developed a clinical score (CS) at Vanderbilt Ingram Cancer Center (VICC) that we hoped would predict outcomes for patients with progressive well-differentiated neuroendocrine tumors (NETs) receiving therapy with Lutetium-177 ( 177 Lu)-DOTATATE. Patients under consideration for 177 Lu-DOTATATE between March 1, 2016 and March 17, 2020 at VICC were assigned a CS prospectively. The CS included 5 categories: available treatments for tumor type outside of 177 Lu-DOTATATE, prior systemic treatments, patient symptoms, tumor burden in critical organs and presence of peritoneal carcinomatosis. The primary outcome of the analysis was progression-free survival (PFS). To evaluate the effect of the CS on PFS, a multivariable Cox regression analysis was performed adjusting for tumor grade, primary tumor location, and the interaction between 177 Lu-DOTATATE doses received (zero, 1–2, 3–4) and CS. A total of 91 patients and 31 patients received 3–4 doses and zero doses of 177 Lu-DOTATATE, respectively. On multivariable analysis, in patients treated with 3–4 doses of 177 Lu-DOTATATE, for each 1-point increase in CS, the estimated hazard ratio (HR) for PFS was 2.0 (95% CI 1.61–2.48). On multivariable analysis, in patients who received zero doses of 177 Lu-DOTATATE, for each 1-point increase in CS, the estimated HR for PFS was 1.22 (95% CI 0.91–1.65). Among patients treated with 3–4 doses of 177Lu-DOTATATE, those with lower CS experienced improved PFS with the treatment compared to patients with higher CS. This PFS difference, based upon CS, was not observed in patients who did not receive 177 Lu-DOTATATE, suggesting the predictive utility of the score.